Fabrication of nano battery from CdS quantum dots and organic polymer - Akeel Kadim (Kuwait Journal of Science)
Rechargeable nano batteries are effective energy storage devices; however, due to the small specific charge ability of the electrode materials, the available energy of current nanomaterial ion batteries is still inadequate for many applications. The energy per surface rechargeable batteries for nanoelectromechanical systems (NEMS) and modern small electronic devices a nano battery is recommended as a stage modification. Cadmium sulfide (CdS) nanocrystals (NCs) or quantum dots (QDs) that was prepared by chemical reaction and were fabricated nano battery device using the TPD / Li: graphite / CdS / Al that was produced by phase segregation method. The optical properties of CdS QDs were described by the spectrometers of ultraviolet-visible (UV-Vis.) and photoluminescence (PL), the results indicate that the QDs prepared were nanocrystalline structures. CdS QDs measured from PL used to have an energy gap (Eg) of 2.69 eV. CdS QDs led to improving the function of the nano battery in terms of enhancing the mobility of the carrier's charging and consequently the processes of recombination between CdS QD and Li-ions. Particular structures can be designed to determine the fundamentals of ion and electron transport for energy storage in nanostructures and to test the limits of three-dimensional nano battery technologies. These key issues are highly difficult to observe and characterize because these batteries contain multiple buried interfaces. One approach for direct observation of ionic phenomena in thin-film batteries is through the production process by a focused ion beam of electrochemically active nano batteries. As such, recent research has established and demonstrated a reliable technique for producing nano batteries. Fabrication of CdS QDs and Li nano battery devices was involved in enhancing the efficiency of the nano battery devices.